2015
DOI: 10.5812/ircmj.18242
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Radiological Findings of Chest X-Ray With Echocardiography in Determination of the Heart Size

Abstract: Background:Heart size is an important and effective parameter in chest X-ray (CXR) interpretation. Studies indicate that, especially in middle-aged men, increased cardiothoracic ratio (CTR) is associated with ischemic heart disease (IHD) and increased rate of morbidity and mortality. The CXR is the most common imaging examination of the heart.Objectives:A good quality posterior-anterior (PA) chest radiograph is an important indicator of the cardiac size. Nowadays, CXR has given its place to more advanced appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In a recent study, we found 12 patients with abnormal chest X-ray with cardiomegaly and pulmonary artery hypertension. Our result of chest X-ray abnormality is nearly consistent with Ali et al study [21]. Echocardiography has played a central role in analyze the morphological and functional change of the cardiac patients with CTD.…”
Section: Discussionsupporting
confidence: 82%
“…In a recent study, we found 12 patients with abnormal chest X-ray with cardiomegaly and pulmonary artery hypertension. Our result of chest X-ray abnormality is nearly consistent with Ali et al study [21]. Echocardiography has played a central role in analyze the morphological and functional change of the cardiac patients with CTD.…”
Section: Discussionsupporting
confidence: 82%
“…Our patient presented with heart failure symptoms which are the commonest presentation of this complication [10]. CXR is not a strong diagnostic procedure as echocardiography, but its availability and a high degree of specificity in the diagnosis of cardiomegaly [11] would be very beneficial for some serious conditions like our case.…”
Section: Discussionmentioning
confidence: 84%
“…Right atrial abnormality was defined as upright P-wave in lead II > 2.5 mm [ 23 ]. The criterion for diagnosis of cardiomegaly from a standard chest X-ray was a cardiothoracic ratio > 0.5 [ 24 ]. In accordance with Thalassemia International Federation guidelines, we defined hemochromatosis using the cardiac T2* technique and magnetic resonance imaging of the liver to determine liver iron concentration (LIC).…”
Section: Methodsmentioning
confidence: 99%
“…These criteria classify patients into heart failure with a preserved ejection fraction (HFpEF), midrange ejection fraction (HFmrEF) and reduced ejection fraction (HFrEF) as shown in supplementary [23]. The criterion for diagnosis of cardiomegaly from a standard chest X-ray was a cardiothoracic ratio > 0.5 [24]. In accordance with Thalassemia International Federation guidelines, we defined hemochromatosis using the cardiac T2* technique and magnetic resonance imaging of the liver to determine liver iron concentration (LIC).…”
Section: Definition and Measurementsmentioning
confidence: 99%